Hacking Criminal Sanctions According to the ITE Law and Islamic Criminal Law - Vicki Dwi Purnomo; Hartanto (Journal of Legal and Cultural Analytics, 2023)
Now we are entering an all-digital era where digital problems and crimes are increasing. This research examines the Law on Information and Electronic Transactions with Islamic Criminal Law according to the Regulations which regulates these actions is Law Number 11 of 2008 regarding Information and Electronic Transactions in Article 31 paragraph (1) to paragraph (2) with penalty criminal Which loaded in Chapter 47 Constitution Number 11 2008 concerning Information and Electronic Transactions, this research was conducted descriptively with the aim of making a better study related to the views of Islamic Criminal Law.